Epidemiology of Kaposi's sarcoma herpesvirus (HHV8) in Vasterbotten county, Sweden - Tedeschi, R; Bidoli, E; Agren, A; Hallmans, G; Wadell, G; De Paoli, P; Dillner, Joakim (Journal of Medical Virology, 2006)
A population-based serosurvey of Human Herpesvirus type 8 (HHV8) in Vasterbotten county, an area of Northern Sweden with high incidence of Kaposi's Sarcoma, was conducted. Serum samples from an age- and sex-stratified random sample of 520 subjects (260 men and 260 women) participating in a population-based biobanking project were tested for antibodies against HHV8, using a sensitive indirect immunofluorescence assay to latent and lytic HHV8 antigens. Buffy coat DNA was also analyzed for viral DNA using real time PCR assay. HHV8 DNA was not detectable in any one of the buffy coat samples. Eighty-four subjects (16.2%) were HHV8 seropositive, 14.4% for the lytic HHV8 antigen, and 1.7% for the latent HHV8 antigen. HHV8 seroprevalences were not associated significantly with sex or age. HHV8 seropositivity was more common among smokers (OR: 1.95, 95% CI: 1.02-3.75), but was less common among consumers of wine and spirits (OR: 0.44,95% CI: 0.25-0.77 and OR: 0.50,95% CI: 0.26-0.95, respectively). In summary, HHV8 has an intermediate high and stable seroprevalence rate in Northern Sweden, but environmental determinants that can explain the viral distribution were not found.